2017
DOI: 10.1038/onc.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived fibulin-3 activates pro-invasive NF-κB signaling in glioblastoma cells and their microenvironment

Abstract: Molecular profiling of glioblastomas has revealed the presence of key signaling hubs that contribute to tumor progression and acquisition of resistance. One of these main signaling mechanisms is the NF-κB pathway, which integrates multiple extracellular signals into transcriptional programs for tumor growth, invasion, and maintenance of the tumor-initiating population. We show here that an extracellular protein released by glioblastoma cells, fibulin-3, drives oncogenic NF-κB in the tumor and increases NF-κB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…[33][34][35][36] However, in human gliomas, EFEMP1 was significantly up-regulated and promoted tumor cell motility and invasion with elevated expression and activity of matrix metalloproteases, such as MMP-2, MMP-9, ADAMTS-5 and ADAM17. [37][38][39] In conclusion, there are reports for prooncogenic and anti-oncogenic roles for EFEMP2, and more in-depth research is needed in the future.…”
Section: Discussionmentioning
confidence: 94%
“…[33][34][35][36] However, in human gliomas, EFEMP1 was significantly up-regulated and promoted tumor cell motility and invasion with elevated expression and activity of matrix metalloproteases, such as MMP-2, MMP-9, ADAMTS-5 and ADAM17. [37][38][39] In conclusion, there are reports for prooncogenic and anti-oncogenic roles for EFEMP2, and more in-depth research is needed in the future.…”
Section: Discussionmentioning
confidence: 94%
“…BAY 11-7082 is a specific pharmacologic NF-κB inhibitor with obvious cytotoxicity, which leads to increasing cell death as the concentration increases [87]. Some studies have shown that BAY 11-7082 impairs alveolar epithelial barrier function and causes unavoidable toxicity in cells and cultured brain tissue [88,89]. In the application of BAY 11-7085 system, toxic reactions were detected, so the local application of NF-κB inhibitor was paid more attention by many scholars.…”
Section: Therapeutic Prospects Of Targeting Inflammasomes In Renal DImentioning
confidence: 99%
“…Ultimately, the Fibulin-3 is an extracellular protein described to be released by GB cells, and its expression is associated with tumor invasiveness and proliferation. Besides, an in vivo study showed that in the core and border of fibulin-3-overexpressed GB occurs the activation of NF-κB in p65+ astrocytes and GB cells ( Nandhu et al, 2017 ).…”
Section: Microglia and Astrocytes’ Role In Glioblastoma Malignancymentioning
confidence: 99%